Key barriers to the implementation of energy-management strategies in building construction projects. Issue 1 (9th April 2018) - Enshassi, Adnan; Ayash, Abed; Mohamed, Sherif
Abstract : Purpose: Knowledge and application of energy management during the life cycle of construction projects are lacking. The purpose of this paper is to identify and investigate the key barriers that are faced by contracting firms in the implementation of energy management during building construction projects focussing on construction plants, as they are considered as the major energy users on site. Design/methodology/approach: A questionnaire survey was employed and distributed using stratified random sampling to 100 contracting companies operating in the Gaza Strip. The collected data were analysed using the Statistical Programme for the Social Sciences (SPSS; Version 22) to identify the number of components that could represent the 31 identified barriers. Findings: From the factor analysis, the barriers were clustered into four factors: economic and financial (which accounted for the largest percentage of variance), knowledge and information, legal and contractual, and organisational and management. This indicates that economic and financial aspects are the most important barrier impeding the implementation of energy management; local contractors should seriously consider this issue when making decisions about energy management during project construction. In addition, the lack of energy-management codes and lack of governmental support are significant obstacles to the implementation of energy management on construction sites. Research limitations/implications: Although the objective of this study was achieved, there were some study limitations. This study is limited to the perceptions and geographical boundaries (i.e. the self-governing territory of Gaza Strip in Palestine as a developing country), therefore, it cannot be generalised. However, it could form the basis for useful comparison in the future. A future study may be carried out with a much larger sample size to validate the conclusions of this study. Triangulation research methods could also be employed in future research in order minimise the bias and validate the conclusion. Further study regarding energy management throughout the whole life cycle of the development is recommended. Practical implications: This paper has highlighted a number of barriers to efficient energy management during the project construction phase. It is critical for local regulators to take note of the economic and financial barriers to facilitate a more energy-conscious society where incentives (could be via tendering preferences) can encourage both clients and contractors to proactively conserve energy during construction. As for the contractual barriers, the local government should lead by example in including "energy consumption" as a leading indicator for evaluating project performance. Originality/value: This study also provides practical knowledge for stakeholders so that they can develop effective methods to overcome the identified barriers to attain higher levels of sustainable energy management. This study can contribute to knowledge in the developing countries context concerning energy management and conservation in construction projects.